HIV‐1 Tat protein induces aberrant activation of AICDA in human B‐lymphocytes from peripheral blood. Issue 9 (31st January 2019) - Sall, Fatimata Bintou; El Amine, Rawan; Markozashvili, Diana; Tsfasman, Tatyana; Oksenhendler, Eric; Lipinski, Marc; Vassetzky, Yegor; Germini, Diego
Abstract: Individuals infected with human immunodeficiency virus (HIV) are at increased risk for Burkitt lymphoma, a B‐cell malignancy which occurs after a chromosomal translocation rearranging the MYC oncogene with an immunoglobulin gene locus, usually the IGH heavy chain gene locus. We have previously reported that the HIV protein Tat which circulates in all HIV‐positive individuals whatever their immune status caused an increased rate of colocalization between IGH and MYC in B‐cells nuclei. We here present in vitro evidence that Tat activates the expression of the AICDA gene that encodes the activation‐induced cytidine deaminase whose physiological function is to create double‐strand breaks for immunoglobulin gene maturation. In the presence of Tat, DNA damage was observed concomitantly in both MYC and IGH, followed by DNA repair by nonhomologous end joining. AICDA was further found overexpressed in vivo in peripheral blood B‐cells from HIV‐infected individuals. Thus, the capacity of Tat to spontaneously penetrate B‐cells could be sufficient to favor the occurrence of MYC‐IGH oncogenic rearrangements during erroneous repair, a plausible cause for the increased incidence of Burkitt lymphoma in the HIV‐infected population. Abstract : We show that human immunodeficiency virus‐1 (HIV‐1) Tat activates the expression of activation‐induced cytidine deaminase whose physiological function is to create double‐strand breaks for immunoglobulin gene maturation in B‐cells. The capacity of Tat to spontaneously penetrate B‐cells could be sufficient to favor the occurrence of MYC‐IGH oncogenic rearrangements during erroneous repair, a plausible cause for the increased incidence of Burkitt lymphoma in the HIV‐infected population.